Neurodevelopmental outcomes of infants with intestinal failure at 12 and 26 months corrected age. (March 2019) - So, Stephanie; Patterson, Catherine; Gold, Anna; Rogers, Alaine; Belza, Christina; de Silva, Nicole; Avitzur, Yaron; Wales, Paul W.
Abstract: Background: Survival rates of infants with intestinal failure (IF) are increasing, yet multiple medical factors may impact development. Aims: This study examines neurodevelopmental outcomes at 12–15 and 26–32 months corrected age in a cohort of children with IF. Study design: Prospective single centre neurodevelopmental assessments of children admitted to an intestinal rehabilitation program between 2011 and 2013. Outcome measures include: Mullen Scales of Early Learning (12 and 26 months), and Vineland-II Adaptive Behaviour Scales - Caregiver Report (26 months). Standard scores were correlated with medical and demographic factors. Results: Thirty-one children (17 males), median gestational age 34 weeks (IQR 30–36) with birth weight (BW) 2.12 kg (IQR 1.24–2.52). Ten (32.2%) were dependent on parental nutrition (PN) at the second assessment. At 12 months, 11/30 (36.7%) scored below average (>1SD below mean) on the early learning composite and 24/30 (80%) were below average on the gross motor subscale. Comparatively, at 26 months, mean early learning scores were significantly lower with >50% scoring below average. Mean gross motor scores remained low, and 14/27 (51.9%) were below average on the Vineland-II motor domain. At 12 months, factors significantly associated with lower scores are primarily related to prematurity. At 26 months, the impact of IF-related variables such as bowel length and PN days are more apparent. Conclusion: Children with IF are at risk of developmental delay in multiple domains. While gross motor skills appear to be most significantly affected, cognitive deficits become more apparent at 26 months, highlighting the importance of early developmental follow up. Highlights: Multiple medical factors can negatively impact neurodevelopment in children with intestinal failure. Gross motor skills appear to be most significantly affected, whereas cognitive deficits become more apparent at 26 months. Early and ongoing comprehensive, developmental follow-up in this population is important.